2012
DOI: 10.1007/s00404-012-2628-4
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral transient osteoporosis of the knee during pregnancy

Abstract: Transient osteoporosis is a rare disease, which can affect pregnant women in the third trimester. Bone marrow edema syndrome, transient bone demineralization, hip algodystrophy, regional migratory osteoporosis, and even reflex sympathetic dystrophy all are terms that have been used to describe the condition. Babinsky and Fromen first documented the symptoms of transient osteoporosis in 1916, and in 1959 Curtiss and Kincaid discussed two cases affecting women in the third trimester of pregnancy. The hip joints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…[7] Although particularly seen in pregnant women during the third trimester, it may also be detected in young men. [7][8][9] The hip joint is most frequently affected (76%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Although particularly seen in pregnant women during the third trimester, it may also be detected in young men. [7][8][9] The hip joint is most frequently affected (76%).…”
Section: Discussionmentioning
confidence: 99%
“…[7] Although particularly seen in pregnant women during the third trimester, it may also be detected in young men. [7][8][9] The hip joint is most frequently affected (76%). [10] This is followed by lower extremity joints such as knee, ankle and foot joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though hip is the most often involved joint, increasingly osteoporosis of knee and talus is also being reported [25,26]. Transient osteoporosis of the hip (TOH) presents acutely in the third trimester of an otherwise normal pregnancy.…”
Section: Hip Painmentioning
confidence: 98%
“…The original description defined the process as transient osteoporosis of the hip (TOH) during pregnancy [3]. The succeeding case reports revealed that TOH may be bilateral [4][5][6][7][8][9][10][11][12] and that may affect not only the hip, but also other joints in the lower extremities, like knee or ankle [13][14][15]. Moreover, it soon became clear that cases were not restricted to pregnancy [16][17][18], or even to women, since the disease was also observed in men, usually in their fifties or sixties [19][20][21].…”
Section: Introductionmentioning
confidence: 99%